DEVELOPMENT OF RURAL AREA BY NGOs PARTICIPATION. CASE STUDY CĂLĂRAȘI COUNTY, ROMANIA - Radu Andrei IOVA; Daniela CREȚU; Oana Roberta CREȚU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the era of globalization, the civil society was recognized as the “third” essential sector regarding its positive influence on the state, but also on the community it represents. The purpose of this study is to analyze and evaluate the way in which members of rural communities perceive the influence of existing NGOs in the commune, on its development. In this sense, we initiated an survey of opinion based on interviews, on a number of 379 respondents from four rural localities in Călărași county, located in different areas of the county and with a different number of NGOs established in the locality, both in number as well as in structure, and we considered the questions: Are there NGOs in the commune? and Do you think that the existence of NGOs can influence the development of your commune?, as edifying to capture the inhabitants' perception on the development of the rural area through the involvement of organized communities, respectively, of NGOs. It should be mentioned that, through this approach, we proposed that, in addition to gather information about the objective of the study, we would also inform the population about the role and importance of the activity carried out by these organizations, to promote the interests of the community they belong to. The research was based on the method of questionnaire survey and χ2 test. Analyzing the answers, it is found that the opinions are very different between the communes (significance threshold very significant), in the sense that those from Modelu and Grădiștea communes know about the existence of NGOs in the community, those from Dragalina commune know about this aspect in a percentage of approx. 50%, while those from Borcea commune do not know or do not know about the existence of these organizations. We find out that more than half of the respondents with higher education are aware of the existence of NGOs in the locality; those with secondary and high school education answered in percentage of 47.87% and those with primary education 30%. The existence of the community organized in the form of an NGO is evaluated differently, significantly, also by male respondents under 45.6% and female respondents in percentage of 56.4%. Through their participatory level, NGOs can support the development of human resources in the rural areas, through training and counseling actions to assist the unemployed workforce in order to reduce unemployment and exploit opportunities on the labor market.